Upaya Pencegahan Deviasi Stok Bahan Baku Antara Sistem dan Aktual Pada Production Floor Plastic Injection (PFPI) di PT X dengan Pendekatan DMAIC - Tedrick Angdjaja; Nova Sepadyati (Jurnal Titra, 2023)
PT X is a plastic manufacturer and the company utilizes SAP system in its operations. Unfortunately, there is still an issue regarding deviation of raw material stock between system and actual inventory. Therefore, this research aims to investigate and analyze the measures that can be taken to prevent the occurrence of such deviation in the Production Floor Plastic Injection (PFPI) PT X. To achieve this objective, the DMAIC approach (Define, Measure, Analyze, Improve, Control) is employed as the framework for the research process. Through the creation of a Fishbone Diagram, several root problems were identified, focusing on method-related factors. These problems include the absence of raw material quantity calculations, lingering overwork (mixer -> setter), inadequate control of good issue and good receipt, and the lack of recording for leftover material transfers. To address these issues, proposed improvement suggestions were formulated, including the implementation of